PENERPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA (Studi Pada Mata Pelajaran IPS Siswa Kelas IV SD Negeri 11 Merapi Barat Lahat) - Fifien Erfianty (UNIB Press, 2020)
Thisstudy aimstoDescribetheapplicationoftheProblemBasedLearning(PBL)learning model,Describetheimprovementof studentlearningincreaseforactivitiesandDescribethe learningachievementsofstudentsatsocialstudiessubjectsin classIVSDNegeri 11Merapi BaratLahat.TheresearchmethodusedwasClassroom ActionResearch(CAR)andquasi- experiments. The research subjects were fourth grade students of semester two of the 2019/2020schoolyearSDNegeri11MerapiBaratLahat.Forquasi-experimentalsamples areclassIVA,classIVBandIVC.Thenumber ofstudentsfor the CARclassis20students, fortheExperimentclassthereare20,andforthecontrol classthereare20students.Data collection methods in this studyused assessment test. Data analysis uses mean means, percentageandt-tests.TheresultsofthestudyshowthatTheapplicationoftheProblem BasedLearningmodel canimprovestudentlearningactivities,Canimprovestudentlearning achievementimprovestudentlearningoutcomesinSopsalScience (IPS)subjects